ADHD in the DSM-5-TR: What has changed and what has not - Athanasios Koutsoklenis; Juho Honkasilta (Frontiers in Psychiatry, 2023)
In this article, we critically review the changes made to the DSM-5 Text Revision published in 2022 regarding the diagnostic entity of Attention Deficit/Hyperactivity Disorder (ADHD). We structure our critique around three points. The first discusses the acknowledgment of ADHD as a neurodevelopmental disorder. The second examines the definition of ADHD provided in the updated edition of the manual. The third scrutinizes the changes in the diagnostic criteria for ADHD and assesses whether these changes make the diagnosis more accurate. We conclude that DSM's latest edition does not escape the logical and scientific pitfalls of its predecessor. DSM-5-TR keeps the faith in the neo-Kraepelinian paradigm by explicitly and implicitly cultivating the essentialist medical scientific metaphor of disorder, creating the illusion that it represents scientific progress that validates ADHD as a neurodevelopmental disorder.